Finding Mary: A Journey of Reclamation - Rumrill, Julie (BookBaby, 2021)
Julie Rumrill was only four when her 16-year-old sister Louise was murdered. Three years later, her 13-year-old sister Mary died as well. Her broken family did what was necessary to survive, and mostly, that meant silence―silence about death, about grief, and about them. For nearly four decades, Julie abided by the family script, burying the memories of her sisters deep within her subconscious. Then, after her dad revealed that he had never been to Mary's grave, she decided they should go together. But there's one major complication: no one actually knows where Mary is buried.Her quest to find Mary leads Julie on a spiritual journey to an Abode in the Appalachians, an Ashram in the Himalayas, and into the darkness of a 250-page police report that recounts her sister Louise's murder. But when a close friend of Julie's is suddenly murdered too, a derailing mix of anger, fear, and guilt surfaces. Desperate to find peace, she's forced to draw on the wisdom of several generations to see this journey to its fruition.
Keywords: dept.esc